2006
DOI: 10.1021/la053218d
|View full text |Cite
|
Sign up to set email alerts
|

From Exponential to Linear Growth in Polyelectrolyte Multilayers

Abstract: There exist two types of polyelectrolyte multilayers: those whose thickness increases linearly with the number of deposition steps, which are nicely structured, and those whose thickness increases exponentially, which resembles hydrogels. This simple picture has recently slightly evolved with the finding that some exponentially growing films enter into a linear growth phase after a certain number of deposition steps. In this study, we investigate the buildup process of hyaluronic acid/poly(L-lysine) (HA/PLL) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
357
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(395 citation statements)
references
References 39 publications
(99 reference statements)
36
357
1
1
Order By: Relevance
“…Furthermore, the film growth follows an exponential regime which is described in more detail elsewhere. 18,24,25 To transform the measured optical thickness ͑n ‫ء‬ d͒ into a film thickness ͑d͒, we assumed a refractive index for the PEM film of 1.42 according to data published by Richert et al 26 The resulting data for the ͑PLL-PGA͒ i film construction are in good accordance with the data reported in the literature in terms of adsorption kinetics and actual layer thickness. 23 After monitoring the PEM film growth in situ ͓dark gray bar framed in white, Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Furthermore, the film growth follows an exponential regime which is described in more detail elsewhere. 18,24,25 To transform the measured optical thickness ͑n ‫ء‬ d͒ into a film thickness ͑d͒, we assumed a refractive index for the PEM film of 1.42 according to data published by Richert et al 26 The resulting data for the ͑PLL-PGA͒ i film construction are in good accordance with the data reported in the literature in terms of adsorption kinetics and actual layer thickness. 23 After monitoring the PEM film growth in situ ͓dark gray bar framed in white, Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Several studies have shown that exponentially growing films will exhibit linear growth after the deposition of ten or more bilayers [21,25,[48][49][50]. It was theorized that exponentially growing films become too thick and evolve three distinct domains within their architecture: Domain I which is in contact with the substrate, Domain III which is at the solution interface and remains permeable to diffusing PE, and eventually Domain II (restructuring zone) which lies between Domains I and III and is constantly in a state of re-organization to a denser film structure making it impermeable to diffusing PE [21,25,48,49]. As a diffusing PE can only permeate so far in a finite amount of time, the film begins to grow linearly [47].…”
Section: Investigation Of Chitosan/hyaluronan (Chi/ha) Film Growth Bymentioning
confidence: 99%
“…Depending on the speed of restructuring, the film may not have time (in solution) to re-establish the preferred hydrated morphology. This has been a concern of more than one author studying the exponential to linear transition; however it was ruled out by Porcel et al who saw no changes in growth rate, mechanism, and film thickness [49]. Despite this revelation, the films used were constructed by a spray method rather than dipping and could be the result of the deposition procedure.…”
Section: Investigation Of Chitosan/hyaluronan (Chi/ha) Film Growth Bymentioning
confidence: 99%
“…11,[25][26][27][28][29] The so-called exponential-like growth of the multilayers is caused by polymer diffusion in and out of the multilayers during the polymer assembly process. [30][31][32][33] The exponential-like growth allows the production of micrometer thick films with high loading capacities for various biomolecules. 10,30 The multilayers can release biomolecules reaching the cells thereby inducing cellular response such as adhesion, migration or differentiation.…”
Section: Introductionmentioning
confidence: 99%